Generation of semantic document model for Quran using ontology domain / Mohd Yunus Mohd Yussof and Hayati Abd Rahman - Mohd Yussof, Mohd Yunus; Abd Rahman, Hayati (Research Management Institute (RMI), 2010)
Ontology has become an important means for structuring knowledge. Based on the methodology, Quran text has been chosen as a case study to carry out the Islamic knowledge through the keywords of English version domain. From the proposed framework, this project able to present on ontology using text based on natural language text for Quran text using Protege 4.